2022
DOI: 10.3390/ijms23094556
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of GPR55 mRNA Expression in Colon Cancer

Abstract: G protein-coupled receptor 55 (GPR55) probably plays a role in innate immunity and tumor immunosurveillance through its effect on immune cells, such as T cells and NK cells. In this study, the prognostic value of GPR55 in colon cancer (CC) was investigated. mRNA expression levels of GPR55 were determined in 382 regional lymph nodes of 121 CC patients with 12 years observation time after curative surgery. The same clinical material had previously been analyzed for expression levels of CEA, CXCL16, CXCL17, GPR35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…RNA from 5 human CC cell lines (HT29, LS174T, Caco2, T84, HCT8), 1 T cell line (Jurkat), 2 B cell lines (CNB6, KR4), 1 monocyte cell line (U937), 1 endothelial cell line (HUVEC) and primary foreskin fibroblasts (FSU) were from previous studies ( 24 29 ).…”
Section: Methodsmentioning
confidence: 99%
“…RNA from 5 human CC cell lines (HT29, LS174T, Caco2, T84, HCT8), 1 T cell line (Jurkat), 2 B cell lines (CNB6, KR4), 1 monocyte cell line (U937), 1 endothelial cell line (HUVEC) and primary foreskin fibroblasts (FSU) were from previous studies ( 24 29 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the high-GPR55/CEA group of patients, an increased survival of 14 and 33 months compared with the low expression group when followed for 5 and 12 years ( p = 0.0003 and p = 0.003), respectively. The authors concluded that that GPR55 may serve as a marker for positive prognosis, either alone or combined with CEA, in CRC [ 3 ].…”
mentioning
confidence: 99%